Relationship between Physical Activity, Knowledge, Attitude, and Nutritional Practice with Body Mass Index (BMI) of Iranian Teenage Girls - Eskandarpour, Fateme Zahra; Younesiyan*, Ali; Delvarianzadeh, Mehri (Shahroud Journal of Medical Sciences, 2023)
Background: Adolescence is considered one of the most critical periods of human development, in which nutrition, physical activity and weight control play a very effective role. This study was conducted to determine the relationship between physical activity, knowledge, attitude and nutritional practice with (BMI) in Student girls. Methods: the statistical population of 270 female students in the age range of 14.3 ± 1.3 in Miami city in 1401 with the convenience sampling method and were selected as available. They completed the questionnaire containing demographic information, knowledge, attitude and nutritional practice (KAP), the international physical activity questionnaire, Anthropometric values (BMI) were computed and compared with CDC2000 standards and then using SPSS software. The significant level was set at 0.05. Results: The results showed that students had 48.7%, 48.1% and 41% moderate score knowledge, practice but attitude score low respectively. Comparison of BMI with standard values showed that 24.5%, 7.7% and 4% of participants were underweight, overweight and obese respectively. Statistically significant correlation was seen knowledge, attitude and nutritional practice with BMI and also between attitude and nutritional practice with physical activity (Pvalue<0.05). Conclusions: Based on the findings, the data indicate that knowledge, attitude and practice nutritional of Mime Shahroud province were moderate or relatively low and all of the students, need more Theoretical and applied nutritional education, physical activity, weight control methods in textbooks and cyberspace is necessary. Keywords, knowledge, Attitude and nutritional practice, Physical activity, Body mass index